O que pensa a criança pequena sobre a escola infantil? - Escariao., Andreia Dutra (2009)
The present study departs from the interest in deepening the studies about the small child, and what it thinks about the children s school. As it forms to develop this research we define as axle the following objectives: To identify what the small child thinks about the children s school; To relate the necessities and expectations of the child with the proposals directed toward Children s Education; To analyze the referring data to the necessities and expectations of the children with regard to children s school with the intention of improvement of the quality of education. We understand that the Children s Education is a fundamental importance stage for the full development of the child. Being thus, our theoretical basis if it gave from the studies of authors who if had considered to write about the small child: Ariès, Kramer, Kuhlmann Jr, among others. As methodological proposal we opt to the study of case of the microethnography type. The sample was a group with eight children, all with five years old, in a school of João Pessoa-PB. We use the comment, drawings as form of expression of the child, the register of the children speechs through recording and questionnaire application with the mothers or the child responsible, with the objective to understand the reasons for which it had the choice of the related children s school. The results had evidenced the expression of the child through the drawing and speech pointing the children s school as a space destined to the learning and the entertainment, the desire of the child in visualizing a rich space in stimulus, colors and forms, the importance of the interaction child/child and child/ adult for the process of full development, as well as the necessity in improving the professionals formation of the children s education, with the intention of getting improvement in the teach quality.